Stock Investment Portfolio Analysis with Single Index Model - Yasir Maulana (Universitas Kuningan, 2020)
In order to evaluate an optimal portfolio, an important step that investors or investment managers is portfolio analysis. In stock portfolio analysis, methods that can be used include the Markowitz approach and the Single Index Model. This study aims to apply the Single Index Model in finding the beta value of an efficient portfolio line, so that investors can determine the stocks and the proportion of funds needed to form an optimal portfolio. In this study, the data sources used were 1) market share price index that represents market factor or market data, 2) SBI interest rates that represents risk free (rf) and 3) The share prices of PT Ace Hardware Indonesia Tbk, PT Indocement Tunggal Perkasa Tbk and PT Matahari Putra Prima Tbk. The weight of each share in the active portfolio (Wi0) at Active Pf A 1.0000 is ACES of 0.1729, INTP of 0.0460 and MPPA of 0.7811. Then the alpha of the ACES active portfolio is 0.0051, INTP is 0.0002 and the MPPA is 0.0184. Then the calculation results show the residual variance in the active ACES portfolio is 0.0041, INTP is 0.0001 and MPPA is 0.0147. The variance of the Optimal Risky Portfolio of the variance index portfolio and the residual variance of the active portfolio is 0.1054.